Quantifying hydrocooling water infiltration in ‘Palmer’ mangoes following hot-air quarantine treatment - Sanches, Alex Guimarães [UNESP]; da Silva, Maryelle Barros [UNESP]; Pedrosa, Vanessa Maria Dantas [UNESP]; Fernandes, Thiago Feliph Silva [UNESP]; Wong, Maria Carolina Casares [UNESP]; Gratão, Priscila Lupino [UNESP]; de Almeida Teixeira, Gustavo Henrique [UNESP] (Elsevier, 2025)
Around the world hot-air heating is used as a quarantine treatment to control fruit fly larvae in mangoes. To simulate hydrocooling water absorption in mangoes subjected to hot-air heating quarantine treatment, the internalization of acid blue 9 dye was tested. Hot-air heating fruits (45 °C) had higher acid blue 9 dye infiltration (2.26 %) compared to untreated control fruits (0.72 %). Higher dye infiltration was observed in heated fruits (2.97 %) after 15 min of cold-water immersion than the 60 min required for 1.84 % infiltration in unheated fruits. Regardless of treatment, dye infiltration occurred uniformly through the lenticels on the pericarp and occasionally through the stem into the mesocarp. Thus, hot-air heating treatment followed by immersion in cold water results in fast water infiltration, potentially allowing the internalization of food-borne pathogens if the cooling water is not properly treated.